Policy rules under the monetary and the fiscal theories of the price-level - Jagjit S. Chadha (University of Kent, School of Economics, 2010)
Price-level determination requires co-ordination of monetary and fiscal policy to ensure a unique rational expectations equilibrium (REE). This paper derives a number of implications for simple interest rate rules resulting from various fiscal strategies. We show that fiscal choices under either the monetary theory of the price-level (MTPL) and the fiscal theory of the price-level (FTPL) can challenge widely accepted principles of monetary policy. Specifically, we show that a fiscal rule that responds aggressively to output and inflation may force the monetary authorities to adopt significantly more aggressive output and inflation stabilization policy than suggested by the Taylor Principle. We also show how when monetary policy is severely constrained, the fiscal policy maker can act to stabilise the economy. Some policy conclusions in light of the lower zero bound for monetary policy and debt stabilization are drawn.
Keywords: E21; E32; E52; E63; 330; monetary and fiscal policy rules; Ricardian fiscal policy; non-Ricardian fiscal policy